Drug Abuse Relapse Rates Linked to Level of Education: Can We Repair Hypodopaminergic-Induced Cognitive Decline With Nutrient Therapy?. Issue 2 (May 2014) - Blum, Kenneth; Schoenthaler, Stephen J.; Oscar-Berman, Marlene; Giordano, John; Madigan, Margaret A.; Braverman, Eric R.; Han, David
Abstract : : It is well known that athletes and other individuals who have suffered painful injuries are at increased risk for all reward deficiency syndrome (RDS) behaviors, including substance use disorder (SUD). Comparing patient demographics and relapse rates in chemical dependence programs is pertinent because demographics may affect outcomes. Increased risk for relapse and lower academic achievement were found to have a significant association in recent outcome data from a holistic treatment center (HTC) located in North Miami Beach, FL. Relapse outcomes from the Drug Addiction Treatment Outcome Study (DATOS; n = 1738) and HTC (n = 224) were compared for a 12-month period. Post-discharge relapse was reported by 26% of HTC patients and 58% of patients in DATOS. When broken out by education level—less than high school, high school diploma, college degree, and graduate degree—HTC patient relapse was 50%, 36%, 33%, and 16%, respectively, and demonstrated an inverse linear association ( F = 5.702; P = 0.017). Looking at DATOS patient relapse rates broken down by educational grades/years completed, patients who attended school between 7th grade and 4 years of college also demonstrated an inverse linear association ( F = 5.563; P = 0.018). Additionally, the lowest performers, patients who reported their academic performance as "not so good, " had the highest relapse ( F = 4.226; P = 0.04). Albeit certain limitations, compared with DATOS patients, HTC patients produced significantly larger net differences in relapse rates ( X 2 = 84.09; P = 0.0001), suggesting that other variables, such as the treatment model may also affect patient relapse. Our results implicate the use of vitamin and mineral supplements coupled with a well-researched natural dopamine agonist nutrient therapy; both have been shown to improve cognition and behavior, and thus academic achievement. That relapse is highest among addicts who have less education and who report lower grades is a factor that can be useful when considering treatment type and controlled for when comparing treatment outcomes.